Hematological and biochemical blood indices of rainbow trout depending on the level of protein in feeds - V. M. Kondratiuk (Тваринництво та технології харчових продуктів, 2021)
Protein nutrition of fish is one of the main factors of ensuring their active growth. Finding the optimal concentration of protein is an actual direction of research. The purpose of the experiment was to establish the effect of different protein nutrition levels in commercial rainbow trout feeding on hematological and biochemical parameters of their blood. For this purpose, five experimental groups were formed by the method of analogs. The experiment lasted 210 days and was divided into two periods: equalization (10 days) and main (200 days). During the equalization period, the feeding ration was the same for fish in the control and experimental groups. In the main period, the level of protein in experimental feeds for different experimental trout groups ranged from 44 to 52% per 1 kg. It was found that different levels of rainbow trout’s protein nutrition did not cause significant changes in blood morphological composition. It is proved that rearing trout using compound feeds with a crude protein content of 50% and 52% promotes the increase of red blood cells, hemoglobin, white blood cells and phagocytic activity in blood. The use of 44% and 46% low crude protein diets in fish feeding reduces the morphological components in blood. As a result of studies on the phagocytic activity of neutrophils in fish blood, a slight increase was revealed under the influence of the studied factor. The analysis of the obtained results showed that with increasing levels of crude protein in the diets of rainbow trout, the concentration of total protein and its fractions in blood serum increased. Accordingly, the amount of total protein in blood of fish in the control group was 60.0 g/L, in the experimental groups – it was within the range of 59.6- 65.3 g/L. The increase in the level of rainbow trout’s protein nutrition in the experimental groups 4 and 5 caused an increase in the number of albumins, β-globulins and γ-globulins compared to control. As a result of experimental studies, an increase in the mineral status of rainbow trout blood during use of feeds with the crude protein content of 50-52 % was established. No differences were found during the assessment of trout white blood cell counts. The use of the obtained results during the production of compound feed will allow having a positive effect on the hematological parameters of commercial rainbow trout